Factors affecting the cost performance of transport infrastructure projects - Eleni Moschouli; Raden Murwantara Soecipto; Thierry Vanelslander; Koen Verhoest (European Journal of Transport and Infrastructure Research, 2018)
The research objective of this paper is to identify the key factors that affect the cost performance of all types of transport infrastructure projects. The method used is the fuzzy set QUALITATIVE COMPARATIVE ANALYSIS (fs QCA), which allows identifying combinations of factors that affect the cost performance. Results show that 30% of the projects, which are on cost, are explained by a good institutional context, a high ability to save costs, high revenue robustness, high transport market efficiency and acceptability and a mostly public financing scheme as core conditions, combined with good governance as peripheral condition. Also, 29% of the projects, which are over cost, are explained by an unfavourable financial-economic context and mostly a private financing scheme as core conditions, combined with inadequate governance as a peripheral condition. In the on-cost analysis, financing scheme and governance appear to be ‘positive’, while in the over-cost analysis, they appear to be ‘negative’, thus acting consistently and showing their importance, since they contribute respectively to the achievement or not of the cost target. These results can provide useful lessons to academics, practitioners, policy makers and all other stakeholders involved in transport infrastructure projects.